Implementasi Tertib Administrasi Pertanahan melalui Program Pendaftaran Tanah Sistematis Lengkap - Diani Kesuma; Rachma Istiana Salsabila; Febri Meutia; Endra Wijaya (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to describe the complete systematic land registration program, including its legal basis, procedures, and obstacles and solutions in its implementation. This study used an empirical legal study method that refers to secondary and primary data. The results of the study indicate that the complete systematic land registration program is based on Law Number 5 of 1960 concerning Basic Agrarian Principles and Regulation of the Minister of Agrarian Affairs and Spatial Planning or the Head of the National Land Agency Number 6 of 2018. The implementation of the complete systematic land registration program includes location and budget preparation, collection of physical and legal data, bookkeeping and certificate issuance, and certificate delivery. Obstacles in the implementation of complete systematic land registration in Cibinong District include a lack of public understanding, differences in land area, limited land history data, and the existence of absentee land. Solutions to overcome obstacles in the implementation of complete systematic land registration include strengthening governance through outreach and cross-agency coordination, structuring transparent financing mechanisms, and updating land data through re-measurement and integration of digital land plot maps.